Immunological mechanisms of tuberculosis susceptibility in TB-infected individuals with type 2 diabetes mellitus: insights from mycobacterial growth inhibition assay and cytokine analysis - Bindu Dasan; Anuradha Rajamanickam; Arul Nancy Pandiarajan; Sivakumar Shanmugam; Sujatha Nott; Subash Babu (Microbiology Spectrum)
ABSTRACT Several studies have highlighted the increased risk of active tuberculosis (TB) in individuals with diabetes mellitus (DM), especially in TB-endemic regions. This dual burden poses significant challenges for TB control efforts. However, there is a lack of reliable laboratory tools to identify individuals at higher risk, and the immunological mechanisms underlying this susceptibility are poorly understood. In this study, we utilized the mycobacterial growth inhibition assay (MGIA) to assess immune response capacity against Mycobacterium tuberculosis (M.tb) in TB infection (TBI) in individuals with type 2 DM (T2DM) (n = 11) compared to those without type 2 DM (NDM) (n = 23). Additionally, we measured various cytokines using multiplex ELISA to understand the immune profile. Our findings revealed that TBI-T2DM individuals exhibited a lower capacity to inhibit M.tb growth compared to TBI-NDM, as evidenced by MGIA results (P = 0.0029). Cytokine analysis further demonstrated diminished production of key cytokines involved in protection, including type 1 (IFNγ, TNFα, IL-2), type 17 (IL-17A), and proinflammatory (IL-1α, IL-1β, IL-6, IL-12p70) cytokines in the TBI-T2DM group compared to TBI-NDM, upon M.tb infection. These findings suggest that MGIA holds promise as an in vitro marker for assessing M.tb immunological control in TBI individuals, particularly those with T2DM. The observed cytokine profile in TBI-T2DM individuals indicates a compromised immune response against M.tb activation, potentially explaining the heightened risk of active TB in this population.IMPORTANCEThis study is important because it sheds light on the impaired immune response in individuals with type 2 diabetes mellitus (T2DM) who are infected with Mycobacterium tuberculosis (M.tb), offering critical insights into why they are at higher risk of developing active tuberculosis (TB). By demonstrating that T2DM individuals exhibit a weakened ability to control M.tb growth and a compromised cytokine profile, the research underscores the need for better diagnostic tools, such as the mycobacterial growth inhibition assay (MGIA), to identify those at greater risk of progression to active TB. The findings also highlight the importance of integrated care strategies for managing both T2DM and TB, particularly in TB-endemic regions, and point to the need for further research to develop more effective interventions tailored to this vulnerable population.